Effect of food quality on tourist satisfaction - Wulandari, R. Indri Dwiani; Hertina, Dede; Hasim, Muhammad Asyraf (International Journal of Psychosocial Rehabilitation, 2020)
This purpose of this research is to investigate the relationship between the extrinsic and intrinsic factors towards tourist satisfaction. Food tourism is getting popular especially in Indonesia where it offered various type of foods from traditional cuisines. There is a high demand on the food explorations among the tourist and therefore it is about time for the service providers to understand the preferences and responses from the tourist with regards to the food quality. The research used qualitative method where questionnaire was used to collect data. Questionnaire distributed among the international tourist upon finishing their meal at selected restaurants. 300 questionnaires distributed with 82% returns rate. The results indicate that both extrinsic and intrinsic factors are equally important and influence towards the tourist satisfaction. Service providers need to learn more about tourist expectations, needs and culture in order to provide the best services in food quality. There is a big opportunity for service providers to sustain in the market and gain more market share should they invest more in accommodating in the food quality matters.